THE RELATIONSHIP BETWEEN SELF-CONTROL AND PHUBBING & SMOMBIE BEHAVIOR IN ADOLESCENTS - Iva Milia Hani Rahmawati; Zulvana Zulvana; Didik Susetiyo Atmojo; Inayatur Rosyidah; Muhammad Taukhid (Jurnal Keperawatan Sriwijaya, 2026)
Aim:  Phubbing" and "smombie" behaviors are consequences of the inability to use technology wisely—specifically, the excessive use of smartphones. Self-control is a crucial aspect to consider regarding phubbing and smombie behaviors; poor self-control often manifests most visibly during social interactions. This study aims to analyze the relationship between self-control and phubbing/smombie behaviors among adolescents at MTsN 1 Kediri. Methods: This is a quantitative study employing a correlational analytic design with a cross-sectional approach, involving a sample of 236 7th and 8th-grade students at MTsN 1 Kediri. Purposive sampling was used as the sampling technique. The Self-Control Scale (SCS) was used to measure self-control, while the Phubbing & Smombie Scale (PS) was used to measure phubbing and smombie behaviors. Data were analyzed using Spearman’s non-parametric correlation test. Results: The study yielded a correlation coefficient (r) of -0.238 with a significance value (p) of 0.278. Since p > 0.05, the null hypothesis (H0) was accepted. This indicates no statistically significant relationship between adolescent self-control and phubbing/smombie behaviors among students at MTsN 1 Kediri. The results reveal a research gap compared to previous studies; while earlier literature suggests a link between self-control and phubbing/smombie behaviors, this study found no significant relationship. The findings suggest that the behavior is driven not by weak self-control, but by factors such as the need for group conformity (fear of appearing unsupportive if one does not check their phone during gatherings) and the requirements of group tasks that necessitate intensive phone use. Conclusion: There is no relationship between self-control and phubbing/smombie behaviors among adolescents at MTsN 1 Kediri.